Control interno de inventarios y su incidencia en la rentabilidad de la empresa credillantas Cotopaxi, cantón La Maná, año 2013 - Calo Pallo, Wilson Genaro (2015)
The research was carried out in the company "CREDILLANTAS COTOPAXI" domiciled in Canton La Mana Av. May 19 and Velazco Ibarra in order to meet the needs of its customers in the urban and rural areas with a different mission to be a leader in the quality products and services based on a manual of functions made by the organization for the functional development of its activities, with the main objective to determine the incidence of internal control of inventories in the profitability of the company "CREDILLANTAS COTOPAXI" La Maná Canton , 2013 for which different research methodologies such as used. Inductive analytical method; research techniques, interviews, observational research; the type of research, descriptive, historical, documentary; research design, no experimental design; and population and sample enabling gather necessary information, and get the results, realizing a letter of authorization for the development of research with a period of approximately five months, then through a plan and program of evaluation of internal control is applied a Assessment questionnaire to the five internal control components (COSO 1) to analyze the accounting system in relation to the NIC as inventory inflows and outflows, which do not comply with the rules for the valuation of stocks; measure the degree of confidence in the application of valuation methods, which has a 59%, with a moderate level of confidence low and measure the level of profitability and its impact on the financial reporting of the company, in which the margin Gross is 20%, the operating margin 13% and net profit is 5% once completed: the application of Accounting Standards, methods for valuing inventories and IFRS to allow proper preparation of financial statements for decision making is recommended and in the same way reduce the level of risk that is evident at the end of the evaluation. Allowing it to be a support tool for the company in order to control and properly manage Inventories for efficient economy.